Evaluation of different polymeric coagulants for the treatment of oil refinery wastewater. Issue 1 (1st January 2020) - Tetteh, E. K.; Rathilal, S.
Abstract: Wastewater from oil refinery industries has major pollution potentials with mutagenic and toxic compounds. Due to water scarcity in South Africa, oil refinery industries are compelled to find appropriate technology to treat their wastewater for reuse. With regards to this, most of the chemo-physical treatment processes are inadequate and are faced with major environmental and economic challenges. Therefore, this study aimed to find replaceable and cost-effective coagulants to the conventional coagulant for the treatment of a local South Africa oil refinery wastewater using dissolved air flotation (DAF) Jar tests. Three polymeric coagulants for the removal of turbidity, total suspended solids, chemical oxygen demand, and soap oil and grease (SOG) were investigated. At defined experimental conditions of recycle ratio (10%), air saturator pressure (350 kPa) and pH at 5, each coagulant was evaluated from a dosage of 10 mg/L to 50 mg/L. Above 80% of the aforementioned oily pollutants were removed at the coagulant dosage of 50 mg/L. Among the coagulants evaluated, PASS was found as the most suitable alternative coagulant to alum, to enhance and aggregate the air bubble–oil droplet interface for easy separation by the DAF. From the results, PASS is foreseen as promising and economical for pre-treatment of industrial wastewater, which is due to its lower cost and easy degradability.